2015
DOI: 10.1089/g4h.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Parent–Child Sexual Health Dialogue with an Intergenerational Game: Parent and Youth Perspectives

Abstract: Objectives: Sexual health discussions between parents and their preadolescent youth can delay sexual debut and increase condom and contraceptive use. However, parents frequently report being uncomfortable talking with their youth about sex, often reporting a lack of self-efficacy and skills to inform and motivate responsible decision making by youth. Intergenerational games may support parent-youth sexual health communication. The purpose of this study was to explore parent and youth perspectives on a proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
(36 reference statements)
1
26
0
Order By: Relevance
“…Regarding their capacity to reinforcing family bond, the included studies showed that intergenerational games can generate new conversational topics, promote positive interaction and communication among family member from different generations [24]. Games can create a shared virtual space, where family members can be updated about the daily life of their relatives through in-game actions that are associated with their real-life activities, which can help to strengthen the family ties [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding their capacity to reinforcing family bond, the included studies showed that intergenerational games can generate new conversational topics, promote positive interaction and communication among family member from different generations [24]. Games can create a shared virtual space, where family members can be updated about the daily life of their relatives through in-game actions that are associated with their real-life activities, which can help to strengthen the family ties [19].…”
Section: Discussionmentioning
confidence: 99%
“…Simply engaging in the game is enough to help draw the focus away from the friction between family members in family interactions. Moreover, a game is perceived as a promising tool to improve positive intergenerational communication on sensitive topics such as sexual health [24].…”
Section: Reinforcing Family Bondmentioning
confidence: 99%
“…One recent study used focus groups with both parents and 11-to-14-year-olds to learn what kind of game features potential users would want in an intergenerational sexual health education game, to be played by parent–child dyads. 63 Nurses can also encourage parents to explore the CDC’s sexual health communication resources (available at www.cdc.gov/teenpregnancy/parent-guardian-resources/index.htm). …”
Section: Calls For Improvementmentioning
confidence: 99%
“…In sexual health education, serious games have been acknowledged to be appealing to adolescents as they are attractive, confidential, and convenient, and can avoid the embarrassment or boredom of discussing the issues with teachers or health promotion educators [ 20 , 21 ]. Scholars [ 22 , 23 ] have identified eight characteristics to be considered when designing effective sexual health education games: (1) individual tailoring, (2) goal setting, (3) narrative or storyline, (4) audio-visual effects, (5) interactivity, (6) challenges at each level, (7) rewards, and (8) immediate feedback.…”
Section: Introductionmentioning
confidence: 99%